ANALYSIS OF THE EFFECTIVENESS OF COLLECTION OF ARTICLE 21 INCOME TAX BY IMPLEMENTING THE SELF ASSESSMENT SYSTEM AT KPP PRATAMA MAKASSAR - Muhammad Mukram (Jurnal Ekonomi, 2022)
The purpose of this study was to determine the effectiveness of Article 21 PPh levies by implementing the Self Assessment System at KPP Pratama Makassar. Primary data is in the form of surveys or observations while secondary data is in the form of data on the number of effective, registered taxpayers and taxpayers who submit SPT obtained from KPP Pratama Makassar. Data analysis used a qualitative descriptive method. Based on the results of the study, it shows that the effectiveness of the three KPP Pratama, if you look at the last 2 years, as measured by the level of effectiveness obtained from the Tax Performance Index (TPI) formula, which is based on tax targets and tax realization, it can be concluded that the results vary widely. Starting from the highest yield that is close to 100% or the very effective category, namely the effective category obtained by KPP Pratama Selatan in 2013 with a total percentage of 92% and KPP Pratama Barat in 2014 with a total percentage of 110%. As for being categorized as ineffective, it was obtained by KPP Pratama Barat in 2013, namely with a total percentage of 52%. Even though KPP Pratama Barat was in the category of ineffective in 2013, in the following year, 2014, it was included in the category of effective.